Recent Advances in Chemical Approaches to the Study of Biological Systems - Shogren-Knaak, Michael A.; Alaimo, Peter J.; Shokat, Kevan M. (Annual Review of Cell and Developmental Biology, 2001)
▪ Abstract A number of novel chemical methods for studying biological systems have recently been developed that provide a means of addressing biological questions not easily studied with other techniques. In this review, examples that highlight the development and use of such chemical approaches are discussed. Specifically, strategies for modulating protein activity or protein-protein interactions using small molecules are presented. In addition, methods for generating and utilizing novel biomolecules (proteins, oligonucleotides, oligosaccharides, and second messengers) are examined.
Keywords: combinatorial chemistry